2009
DOI: 10.1177/0091270009332811
|View full text |Cite
|
Sign up to set email alerts
|

Limited Sampling Strategies for the Estimation of Sirolimus Daily Exposure in Kidney Transplant Recipients on a Calcineurin Inhibitor—Free Regimen

Abstract: Sirolimus (SRL) is a novel immunosuppressive agent characterized by a narrow therapeutic index. Monitoring of SRL concentrations is mandatory to optimize drug dosing. The area under the concentration-time curve (AUC) is generally accepted as the best pharmacokinetic marker of daily drug exposure. Assessment of full SRL AUC, however, requires the collection of multiple blood samples, imposing both time and cost constraints. Limited sampling strategies (LSS) may be of clinical relevance to improve the therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Trough concentration (C trough ) and AUC correlation appears reasonable [16], although others have reported poorer correlation [52]. By contrast, AUC monitoring is often laborious and patient unfriendly unless limited sampling is applied.…”
Section: Sirolimusmentioning
confidence: 97%
“…Trough concentration (C trough ) and AUC correlation appears reasonable [16], although others have reported poorer correlation [52]. By contrast, AUC monitoring is often laborious and patient unfriendly unless limited sampling is applied.…”
Section: Sirolimusmentioning
confidence: 97%
“…If the differences within mean ±1.96 × the standard deviation are not clinically important, the 2 methods may be used interchangeably. 1,16,33 All statistical analyses were performed with the use of the Statistical Package for the Social Sciences 13.0 for Windows (SPSS, Chicago, Ill).…”
Section: Pharmacokinetics and Statistical Analysismentioning
confidence: 99%
“…The aim of this study was to evaluate whether single concentrationtime points could adequately predict moclobemide systemic exposure. Pharmacokinetic data (full 7-point pharmacokinetic profiles), obtained from 21 depressive inpatients receiving moclobemide (150 mg 3 times daily), were randomly split into development (n = 18) and validation (n = 16) sets. Correlations between the single concentrationtime points and the area under the concentration-time curve within a 6-hour dosing interval at steady-state (AUC 0-6 ) were assessed by linear regression analyses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic polymorphism of these enzymes and combination of drug therapy can affect plasma concentrations of mTOR and may lead to toxicities or treatment failure [89,90]. Cattaneo et al analyzed 2658 sirolimus trough samples in 495 kidney transplant recipients and found that dose-normalized sirolimus trough concentrations were significantly higher in patients treated with cyclosporine and sirolimus, compared with patients treated with mycophenolate mofetil and sirolimus or with patients treated with steroids and sirolimus [91]. They also showed that mean intra-and interpatient variability was 19 and 47%, respectively.…”
Section: Mtor Inhibitorsmentioning
confidence: 99%